2014
DOI: 10.1007/s40430-013-0122-y
|View full text |Cite
|
Sign up to set email alerts
|

The feedback effect caused by bed load on a turbulent liquid flow

Abstract: Experiments on the effects due solely to a mobile granular layer on a liquid flow are presented (feedback effect). Nonintrusive measurements were performed in a closed conduit channel of rectangular cross section where grains were transported as bed load by a turbulent water flow. The water velocity profiles were measured over fixed and mobile granular beds of same granulometry by Particle Image Velocimetry. The spatial resolution of the measurements allowed the experimental quantification of the feedback effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…The cross-sectional mean velocities of water U were within 0.226 m/s and 0.312 m/s, corresponding to Reynolds numbers based on the channel height (Panton, 2010), Re = ρU2δ/μ, within 1.13 × 10 4 and 1.55 × 10 4 , respectively, and to Stokes numbers (Andreotti et al, 2013) St t = Udρ s /(18μ) within 6.3 and 35.5, where ρ is the density and μ the dynamic viscosity of the fluid. The shear velocities on the channel walls u * (base flow) were computed from velocity profiles measured in previous works with a two-dimensional particle image velocimetry device (Alvarez & Franklin, 2018;Cúñez et al, 2018;Franklin et al, 2014), and were found to follow the Blasius correlation (Schlichting, 2000), from which we found 0.0133 m/s ≤ u * ≤ 0.0168 m/s. This corresponds to Reynolds numbers at the grain scale, Re * = ρu * d/μ, within 3 and 8 and to Shields numbers, θ = 𝐴𝐴 ( 𝜌𝜌𝜌𝜌 2 * ) ∕((𝜌𝜌𝑠𝑠 − 𝜌𝜌)𝑔𝑔𝑔𝑔) , within 0.060 and 0.086.…”
Section: Methodsmentioning
confidence: 77%
“…The cross-sectional mean velocities of water U were within 0.226 m/s and 0.312 m/s, corresponding to Reynolds numbers based on the channel height (Panton, 2010), Re = ρU2δ/μ, within 1.13 × 10 4 and 1.55 × 10 4 , respectively, and to Stokes numbers (Andreotti et al, 2013) St t = Udρ s /(18μ) within 6.3 and 35.5, where ρ is the density and μ the dynamic viscosity of the fluid. The shear velocities on the channel walls u * (base flow) were computed from velocity profiles measured in previous works with a two-dimensional particle image velocimetry device (Alvarez & Franklin, 2018;Cúñez et al, 2018;Franklin et al, 2014), and were found to follow the Blasius correlation (Schlichting, 2000), from which we found 0.0133 m/s ≤ u * ≤ 0.0168 m/s. This corresponds to Reynolds numbers at the grain scale, Re * = ρu * d/μ, within 3 and 8 and to Shields numbers, θ = 𝐴𝐴 ( 𝜌𝜌𝜌𝜌 2 * ) ∕((𝜌𝜌𝑠𝑠 − 𝜌𝜌)𝑔𝑔𝑔𝑔) , within 0.060 and 0.086.…”
Section: Methodsmentioning
confidence: 77%
“…Those upper and lower bounds were fixed to allow bed load and, at the same time, avoid the fast formation of ripples on the granular bed. The water flow profiles presented in Franklin et al (2014a) were assumed to be valid for the present experiments and are used here.…”
Section: Experimental Devicementioning
confidence: 99%
“…For example, the water stream is responsible for the solid discharge, which, by its turn, modifies the morphology of the bed by erosion and sedimentation processes (Franklin, 2012). Other example is the modification of the fluid flow by momentum transfers from the fluid to the moving grains, and from the latter to the fixed part of the bed, known as feedback effect (Franklin et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation